2020
DOI: 10.1111/jpn.13402
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism of red clover isoflavones in rumen fluid

Abstract: Isoflavones are plant secondary metabolites that take part in plant defence mechanisms, have functions in attraction of pollinators (Daems, Decruyenaere, et al., 2016) or establish the symbiotic relationship between the plant and rhizobial bacteria to form root nodules (Yu et al., 2000). Moreover, they also have numerous human health benefits (Adler et al., 2014). Because of their similarity to 17β-estradiol, these polyphenolic compounds are a part of a group called phyto-oestrogens (Daems, Romnee, et al., 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Similarly, rapid degradation of formononetin, daidzein, biochanin A and genistein within 4 to 6 h of incubation in rumen fluid was described in early study of Dickinson et al (1988). Further, recent studies of Trnková et al (2018) and Dadáková et al (2020) confirmed this rapid metabolism of isoflavones manifested also by the increases in equol production starting after about 3 h of incubation in rumen fluid in vitro. Degradation rate of daidzein and genistein in the rumen found in our study corresponds with the half-lives of those isoflavones in the rumen fluid determined by Dickinson et al (1988), being 9.3 h for daidzein and 5.5 h for genistein.…”
Section: Except Of Factors Mentioned Above Influencing the Compositionmentioning
confidence: 65%
See 1 more Smart Citation
“…Similarly, rapid degradation of formononetin, daidzein, biochanin A and genistein within 4 to 6 h of incubation in rumen fluid was described in early study of Dickinson et al (1988). Further, recent studies of Trnková et al (2018) and Dadáková et al (2020) confirmed this rapid metabolism of isoflavones manifested also by the increases in equol production starting after about 3 h of incubation in rumen fluid in vitro. Degradation rate of daidzein and genistein in the rumen found in our study corresponds with the half-lives of those isoflavones in the rumen fluid determined by Dickinson et al (1988), being 9.3 h for daidzein and 5.5 h for genistein.…”
Section: Except Of Factors Mentioned Above Influencing the Compositionmentioning
confidence: 65%
“…Production of metabolites can be observed after 3 h of incubation in the rumen fluid in vitro (Dadáková et al, 2020;Trnková et al, 2018).…”
mentioning
confidence: 99%
“…Therefore, milk and dairy products can be considered to be a source of equol for humans not able to produce this metabolite [ 53 , 54 ]. However, for the purposes of functional food production, the feed of dairy cattle, as well as milk processing should be considered, as these parameters substantially influence equol concentrations [ 53 , 55 , 56 ].…”
Section: Roles Of Isoflavones In Human Healthmentioning
confidence: 99%
“…Dietary isoflavones are extensively metabolized in the rumen by ruminal microorganisms [ 51 ]. Their half-lives in the bovine rumen fluid are 4.3 h for formononetin, 9.3 h for daidzein, 3.9 h for biochanin A, and 5.5 h for genistein [ 84 ] and their metabolites occur after 3 h of incubation in the rumen fluid in vitro [ 55 , 56 ]. Concerning the main metabolites, formononetin is demethylated to daidzein, and then further metabolized to equol, a compound with significant estrogenic activity, while biochanin A is demethylated to genistein and further converted to p-ethyl-phenol with no estrogenic activity [ 5 ].…”
Section: Factors Affecting the Content Of Isoflavones In Bovine MImentioning
confidence: 99%
See 1 more Smart Citation